Spatial distribution of selected soil features in Hajdú-Bihar county represented by digital soil maps - Pásztor, László; Laborczi , Annamária; Takács, Katalin; Szatmári, Gábor; Illés, Gábor; Fodor, Nándor; Négyesi, Gábor; Bakacsi, Zsófia; Szabó, József (Acta Geographica Debrecina Landscape & Environment series, 2016)
With the ongoing DOSoReMI.hu project we aimed to significantly extend the potential, how soil information requirements could be satisfied in Hungary. We started to compile digital soil maps, which fulfil optimally general as well as specific national and international demands from the aspect of thematic, spatial and temporal accuracy. In addition to relevant and available auxiliary, spatial data themes related to soil forming factors and/or to indicative environmental elements we heavily lean on the various national soil databases. The set of the applied digital soil mapping techniques is gradually broadened. In our paper we present some results in the form of brand new soil maps focusing on the territory of Hajdú-Bihar county.